Commissioning the HTCondor-CE for the Open Science Grid. Issue 6 (December 2015) - Bockelman, B; Cartwright, T; Frey, J; Fajardo, E M; Lin, B; Selmeci, M; Tannenbaum, T; Zvada, M
Abstract: The HTCondor-CE is the next-generation gateway software for the Open Science Grid (OSG). This is responsible for providing a network service which authorizes remote users and provides a resource provisioning service (other well-known gateways include Globus GRAM, CREAM, Arc-CE, and Openstacks Nova). Based on the venerable HTCondor software, this new CE is simply a highly-specialized configuration of HTCondor. It was developed and adopted to provide the OSG with a more flexible, scalable, and easier-to-manage gateway software. Further, the focus of the HTCondor-CE is not job submission (as in GRAM or CREAM) but resource provisioning. This software does not exist in a vacuum: to deploy this gateway across the OSG, we had to integrate it with the CE configuration, deploy a corresponding information service, coordinate with sites, and overhaul our documentation.